Cross‐genotype‐specific T‐cell responses in acute hepatitis E virus (HEV) infection. Issue 4 (8th February 2016) - Gisa, A.; Suneetha, P. V.; Behrendt, P.; Pischke, S.; Bremer, B.; Falk, C. S.; Manns, M. P.; Cornberg, M.; Wedemeyer, H.; Kraft, A. R. M.
Summary: Hepatitis E is an inflammatory liver disease caused by infection with the hepatitis E virus (HEV). In tropical regions, HEV is highly endemic and predominantly mediated by HEV genotypes 1 and 2 with >3 million symptomatic cases per year and around 70 000 deaths. In Europe and America, the zoonotic HEV genotypes 3 and 4 have been reported with continues increasing new infections per year. So far, little is known about T‐cell responses during acute HEV genotype 3 infection. Therefore, we did a comprehensive study investigating HEV‐specific T‐cell responses using genotypes 3‐ and 1‐specific overlapping peptides. Additional cytokines and chemokines were measured in the plasma. In four patients, longitudinal studies were performed. Broad functional HEV‐specific CD4 + and CD8 + T‐cell responses were detectable in patients acutely infected with HEV genotype 3. Elevated of pro‐ and anti‐inflammatory cytokine levels during acute HEV infection correlated with ALT levels. Memory HEV‐specific T‐cell responses were detectable up to >1.5 years upon infection. Importantly, cross‐genotype HEV‐specific T‐cell responses (between genotypes 1 and 3) were measurable in all investigated patients. In conclusion, we could show for the first time HEV‐specific T‐cell responses during and after acute HEV genotype 3 infection. Our data of cross‐genotype HEV‐specific T‐cell responses might suggest a potential role in cross‐genotype‐specific protection between HEV genotypes 1 and 3.